Conclusion from the Doctor's Dissertation Martynov V.L. on Surgical Correction of Digestive System Refluxes - Martynov Vladimir Leonidovich (Journal of Human and Animal Intestines, 2021)
Annotation On the basis of 40 years of work on the treatment of 415 patients with gastroenterocolitis clinic, the author revealed the presence of refluxes due to anatomical defects of the Bauhinia valve (its failure) and the duodenum (chronic duodenal obstruction) at all levels of the gastrointestinal tract. After surgical correction of these anatomical breakdowns, the author states a significant improvement in all indicators of the state of both the digestive system and some extraintestinal manifestations, possibly the onset of precancer. The results obtained allowed the author to conclude that there are no
Keywords: Digestive System Reflux